On the combined use of nanoparticles and a proper solvent/non-solvent system in preparation of superhydrophobic polymer coatings. (15th January 2015) - Seyfi, Javad; Hejazi, Iman; Jafari, Seyed-Hassan; Khonakdar, Hossein Ali; Mohamad Sadeghi, Gity Mir; Calvimontes, Alfredo; Simon, Frank
Abstract: A novel method including combined use of nanoparticles and non-solvent is proposed for fabrication of superhydrophobic polystyrene coatings. The proposed method results in utterly homogenous and mechanically stable coatings with excellent adhesion to the substrate as compared to the other commonly used solution-based methods. It is proved that individual use of nanoparticles and non-solvent could lead to superhydrophobic behavior but at the price of adding very high contents. Based on water contact angle results, the proposed method causes a significant reduction in the required contents of nanoparticles (150 wt% to 20 wt% with respect to the polymer) and non-solvent (33 vol% to 9–16 vol%) for achieving superhydrophobicity. A thorough investigation of surface composition and morphology is also conducted via X-ray photoelectron spectroscopy (XPS) and scanning electron microscopy (SEM), respectively. Moreover, a different approach is employed for evaluation of surface topography using diverse roughness parameters. It was found that a combination of roughness parameters should be considered for a proper surface analysis instead of only using average roughness and root mean square. It was also demonstrated that the surface roughness uniformity is another key factor to achieve a self-cleaning behavior. Graphical abstract: Highlights: A novel method for fabricating superhydrophobic nanocomposite coatings is presented. A full set of roughness parameters should be regarded for a proper surface analysis. Opposed to other similar coatings, such method gives highly homogenous appearance. Combining nanoparticle and non-solvent had a synergistic effect on phase separation.